Strategi Mitigasi Risiko Koreksi Fiskal: Perspektif Konsultan Pajak dalam Era Digitalisasi Administrasi Perpajakan - Atin Friatna; Se Tin (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to analyze the role of tax consultants in assisting taxpayers, both corporate and individual, in identifying and mitigating the risk of fiscal corrections from the tax reporting stage. The implementation of the self-assessment system in Indonesia requires a high level of compliance and reporting accuracy, while regulatory complexity and the digitalization of tax administration increase the potential for fiscal errors. This study employs a qualitative approach using purposive sampling, involving 25 tax consultants who are members of the Indonesian Tax Consultants Association (IKPI) Bandung. Data collected through semi-structured interviews and analyzed using thematic analysis. The findings indicate that tax consultants play a strategic role in fiscal education, verification and enhancement of data quality, early detection of fiscal correction risks, and the formulation of compliance and tax planning strategies. Proactive assistance provided from the reporting stage shown to minimize the potential for fiscal corrections and tax disputes. However, the effectiveness of such assistance still faces challenges, including low taxpayer tax literacy, limited data quality, administrative system constraints, and differences in interpretation with tax authorities. This study underscores the importance of tax consultants as strategic partners in strengthening compliance and the accuracy of fiscal reporting.